Prevention Versus Treatment of Intrathecal Morphine-induced Pruritus With Ondansetron. Issue 3 (September 2015) - Kung, A.T.; Yang, X.; Li, Y.; Vasudevan, A.; Pratt, S.; Hess, P.
Abstract : ( Int J Obstet Anesth . 2014;23(3):222–226)